KINERJA DEWAN PERWAKILAN DAERAH (DPRD) KABUPATEN BOLAANG MONGONDOW TAHUN 2016 - Moh. Syahruddin Mokoagow (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
The Regional People's Legislative Assembly is an institution that places the hope in bringing about change and the welfare of society. In this study the author explains, describes and analyzes the performance of Bolaang Mongondow District People's Legislative Assembly case study of fiscal year 2016. In improving the function of legislation, the Regional PeopleÔÇÖs Legislative Assemby should be pro-active to absorb the aspirations that are accommodated in the local regulations embodied in the initiative. On the budget function, the Regional PeopleÔÇÖs Legislative Assemby can provide motivation and innovation to the executive to increase the source of local revenue. On the oversight function, the Regional PeopleÔÇÖs Legislative Assemby should be concrete and realistic report violations of criminal/civil law on the implementation of government to law enforcement. Furthermore, interpellation rights, questionnaire rights and the right to express opinions regarding important and strategic issues concerning the interests and welfare of Bolaang Mongondow community.